Knowledge of Child adoption services in civil servants in Ibadan, Nigeria. (2019)
Adoption provides an alternative for childless couples to have their own children, but the knowledge of this option and its services affects people’s choice. This study assessed the awareness and depth of knowledge of adoption among 403 civil servants working in the Oyo State Secretariat, Ibadan, Nigeria. This was a descriptive cross-sectional study conducted between February and May, 2008. Self-administered questionnaire was used to collect data on socio-demographic characteristics, knowledge of child adoption, laws and services. Each correct knowledge question had a score of 1 and each wrong knowledge question had a score of 0. Total scores were computed for each respondent. Knowledge scores which ranged from 0-5 and from 6-13 were considered low and high, respectively. Descriptive and Chisquare statistics were used for data analysis.Mean age of respondents was 40.2 ± 9.7 years. Sixty five percent had tertiary education, 77.4% were married, and 53.3% were senior civil servants. Majority (91.8%) had heard about child adoption; of these 65.1% could correctly state its meaning. Sixty three percent were aware of adoption services; of these, 33.0% knew where adoption services were provided and 47.3% were aware of adoption laws. Also (41.1%) knew someone that had adopted a child. Overall, 16.9% had high knowledge scores. Respondents who had tertiary education were more knowledgeable about adoption than others (p< 0.05). Majority of respondents were aware of child adoption services but knowledge of the details was low. Efforts should be made to enlighten the public about adoption.